Non-Suicidal Self-Injury (NSSI) Patterns in Adolescents from a Romanian Child Psychiatry Inpatient Clinic - Lucia Emanuela Andrei; Magdalena Efrim-Budisteanu; Ilinca Mihailescu; Alexandra Mariana Buică; Mihaela Moise; Florina Rad (MDPI AG, 2024)
Non-Suicidal Self-Injury (NSSI) involves deliberately causing harm to one's body without the intention of suicide. As the numbers of adolescents presenting NSSI have been steadily increasing during the last years, we intended to investigate adolescent patients exhibiting NSSI, admitted to our clinic-a Romanian child psychiatry inpatient clinic, over the course of five years. A total of 100 adolescents (80 females, 20 males, mean age: 14.9 years) hospitalized for various neuropsychiatric disorders and engaging in self-harm were studied. The self-harm methods most frequently used in our sample were, for the female group: cutting (all), skin tearing (76%), scratching/pinching (72%), and for males: cutting (all), wound-healing hindrance (85%), striking objects (80%). The initial motivations for NSSI were represented by distress (females 89%, males 90%) and seeking pleasure (females 84%). In terms of the roles of NSSI, it was primarily used for emotional regulation (females 89%) and anger management (males 90%). This study highlights the prevalence of self-harm in hospitalized adolescents, differences in methods and motivations between genders, and the need for more targeted therapy interventions. By documenting trends, investigating underlying motivations and functions, and proposing hypotheses for further research, our findings offer valuable insights on adolescent NSSI and have the potential to increase awareness among various clinicians and specialists who interact with adolescents, thus addressing the escalating prevalence of self-harm behaviours among teenagers.